Cultural Values of the North Maluku Society in the Legend of "Telaga Biru": A Folklore Study - Nisa Siti Nurramadhani; Anggun Maharani Putri; Zahra Rayhana Fauziah; Pandu Insan Firdaus (Litteratura: Jurnal Bahasa dan Sastra, 2026)
As part of the community's oral tradition, the Legend of Telaga Biru holds cultural values that are important to record and preserve, especially given the shift in how the story is told, from an oral to a written form. This study aims to describe the representation of North Maluku society's cultural values in the Legend of Telaga Biru through a folklore study. The primary data consist of the text of the Telaga Biru legend from Galela, North Halmahera, obtained from cultural portals and online media published between 2022 and 2025, while supporting data consist of journal articles from the last five years on cultural values, local wisdom, and the use of folklore. This study employs a descriptive qualitative method with reading, note-taking, classification, and interpretation techniques. The analysis was carried out through a folklore approach and representation analysis to identify narrative elements, characters, settings, conflicts, the symbol of water, and social functions in the Telaga Biru legend. The results show that the Legend of Telaga Biru represents the values of loyalty, responsibility toward promises, fortitude, communal solidarity, respect for customary traditions, and ecological awareness. The lake is present not merely as a natural setting but as a symbol of collective memory that connects the characters' personal experience with the community's livelihood needs. This legend also functions as a medium for character education, the strengthening of Galela's local identity, and a reminder of the importance of preserving water sources as a cultural space. A limitation of this study lies in its reliance on secondary written data, which has not yet captured the full variation of the local community's oral narration. Keywords: Legend of Telaga Biru; cultural values; folklore; North Maluku; local wisdom